Pengaruh Good Corporate Governance Dan Kepemilikan Institusional Terhadap Kinerja Keuangan Perusahaan Asuransi - Jayanti Dwi Lestari; Erna Sulistyowati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research aims to explain and analyze the influence of independent commissioners on the financial performance of insurance companies listed on the Indonesia Stock Exchange in 2016 - 2020. The variables used are independent commissioners, board of directors, audit committees, institutional ownership as independent variables, and financial performance (ROA) as dependent variables. Sample determination using the purposive sampling method with a sample of 10 companies. The data analysis techniques used are descriptive statistical analysis, normality test, classical assumption test, multiple linear regression analysis, model match test (F test), determination coefficient test (), partial test (t Test). The results of this study show that independent Commissioners, board of directors, institutional ownership affect financial performance (Return On Asset) in Insurance Companies. While the audit committee has no effect on financial performance (Return On Asset) in Insurance Companies. Keywords: Good Corporate Governance, Independent Commissioner, Board of Directors, Institutional Ownership, Audit Committee